Optimization Of Cutting Condition In The Turning Of AISI D2 Steel By Using Carbon Nanofiber Nanofluid - Liew, Pay Jun; Shaaroni, Ainusyafiqah; Abd Razak, Jeefferie; Kasim, Mohd Shahir; Sulaiman, Mohd Amri (Research India Publications, 2017)
-